2013
DOI: 10.1111/nyas.12034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of antibody development in renal transplantation

Abstract: The detection and characterization of anti-HLA antibodies and the clinical impact of their appearance following renal transplantation are areas of immense interest. In particular, de novo development of donor-specific antibodies (DSA) has been associated with acute and chronic antibody-mediated graft rejection (AMR). Recently, methods for antibody detection have evolved remarkably from conventional cell-based assays to advanced solid phase systems. These systems have revolutionized the art of defining clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 90 publications
1
16
0
1
Order By: Relevance
“…Anti-HLA antibodies have been considered a risk factor for acute or hyperacute rejection and poor long-term allograft survival (Hyun et al, 2012). HLA alloimmunization is known to be associated with various sensitization events such as pregnancy, blood transfusion, and transplantation (Triulzi et al, 2009;Mehra et al, 2013;Valenzuela et al, 2013). Recent studies have shown that the prevalence of leukocyte antibodies increases with pregnancies, and blood transfusion is also associated with a minor increase in leukocyte antibody prevalence (Middelburg, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Anti-HLA antibodies have been considered a risk factor for acute or hyperacute rejection and poor long-term allograft survival (Hyun et al, 2012). HLA alloimmunization is known to be associated with various sensitization events such as pregnancy, blood transfusion, and transplantation (Triulzi et al, 2009;Mehra et al, 2013;Valenzuela et al, 2013). Recent studies have shown that the prevalence of leukocyte antibodies increases with pregnancies, and blood transfusion is also associated with a minor increase in leukocyte antibody prevalence (Middelburg, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…As ECs are the primary targets for alloimmune attack following transplantation [4245], we will focus our discussion on injury to ECs of the microvasculature. We will discuss in detail the mechanisms by which immune cells, antibodies, complement factors, oxidative stress, and immunosuppressive drugs induce EC injury.…”
Section: Microvascular Ec Injury In Transplantationmentioning
confidence: 99%
“…4 Furthermore, they can influence the outcome of cell and organ transplantations. 7 Class I molecules are responsible for the presentation of peptides derived from the inner part of the cell to the CD8 + T cells.…”
Section: Importance Of Pregnancy Inducedmentioning
confidence: 99%